Qualitative analysis of the risks and practices associated with the spread of African swine fever within the smallholder pig value chains in Uganda - Dione, Michel M.; Ouma, Emily A.; Opio, F.; Kawuma, Brian; Pezo, Danilo A. (Elsevier, 2016)
A study was undertaken between September 2014 and December 2014 to assess the perception of smallholder pig value chain actors of the risk of African swine fever (ASF) disease, and practices that are associated with its spread within the pig value chains. Data was collected from 136 value chain actors and 36 key informants through 17 group discussions and two key informant interview (KII) sessions respectively using Participatory Rural Appraisal (PRA) tools. Results from this study revealed that according to value chain actors and stakeholders, the transportation, slaughtering, and collection/bulking nodes represent the highest risk, followed by the inputs and services (feeds and drugs) supply nodes. The processing, whole sale and consumption nodes represented the lowest risk. Value chain actors are aware of the disease and its consequences to the pig industry, however biosecurity measures are poorly implemented at all nodes of the value chain. As for the causes, value chain actors pointed to several factors, such as inadequate knowledge of mechanisms for the spread of the disease, poor enforcement of regulations on disease control, and low capacities of actors to implement biosecurity measures, amongst others. Although traders, butchers and veterinary practitioners accepted that they played an important role in the spread of the virus, they did not perceive themselves as key actors in the control of the disease; instead, they believed that only farmers should adopt biosecurity measures on their farms because they keep the pigs for a longer period. Most of the recommendations given by the value chain actors for controlling and preventing ASF disease were short term, and targeted mainly pig producers. These recommendations included: the establishment of live pig collection centres so that traders and brokers do not have to directly access pig farms, capacity building of value chain actors on application of biosecurity, enactment and enforcement of by-laws on live pig movements and establishment of operational outbreak reporting mechanism at district level. Long term recommendations included the development of a vaccine, as well as pen-side diagnostic tests. This study suggests that interventions to control ASF disease through application of biosecurity measures should target all value chain actors, but should put more emphasis on post-farm nodes especially the trading.